Estimativa do conteúdo de água no solo, evapotranspiração e produtividade primária bruta por reanálise e sensoriamento remoto nos biomas de Mato Grosso - Ivo, Israel Oliveira (2024)
Reliable satellite data and large-scale estimates of microclimate variables have been a growing need for microclimate studies in Mato Grosso. The region, which is home to three important Brazilian biomes, is undergoing an intense process of landscape modification. Understanding the effects of the modification of these areas of native vegetation on energy and mass fluxes, as well as their drivers, is of paramount importance for the development of natural resource management policies. This study evaluated estimates of soil water content (WS), evapotranspiration (ET) and gross primary productivity (GPP) in natural and anthropized formation areas in Mato Grosso. Estimates were obtained from reanalysis products, remote sensing, and the Thermal-Optical Trapezoid Model (TOTRAM). These data were also grouped into multi-model ensembles (MME) to generate new estimates. The results of the study are presented in two papers, the first evaluating the SM estimates and the second evaluating the ET and GPP estimates. Combining the SM, ET, and GPP products in the MME produced estimates with higher correlation, better agreement, and lower errors, while preserving the spatial variability of the products. The SSEBop, GLEAM, and PML products and the MME had the best validation performance, especially in the Pantanal. The research concluded that MME estimates provide more reliable and comprehensive data, allowing the study of regions that are difficult to access or more remote locations. These results also provide society with a safer alternative for developing sustainable natural resource management projects. The results have provided a clearer understanding of which data are most appropriate for the region, how these quantities have evolved, and what future scenarios exist in relation to the dynamics of water and carbon flows in Mato Grosso.